Teaching and learning sensitive and controversial topics in history through and with decolonial love (Yesterday & Today Journal for History Education in South Africa and abroad, 2023)
The Curriculum and Assessment Policy Statement (CAPS) school history curriculum of post-apartheid South Africa is littered with sensitive and controversial topics. Many history teachers and their learners do not know how to confront these topics, especially in multiracial, multicultural, and diverse classrooms. Therefore, this paper explores how the idea of decolonial love (Sandoval, 2000; Maldonado-Torres, 2006) could inform alternative creative pedagogies or contribute to existing pedagogical frameworks that history teachers and their learners employ when engaging sensitive and controversial topics. In this paper I argue that decolonial love has the potential to enable both history teachers and their learners to engage with sensitive and controversial topics in history in ways that promote empathy, cognitive, social and epistemic justice, inclusivity, critical thinking, respect, love, and tolerance for others as envisioned in the CAPS document. This would, in turn, promote the transgression of knowledge boundaries for knowledge co-construction (Keating, 2013) and thus, enable a way of doing history that promotes pluriversal (situated) knowledges (Santos, 2014). Lastly, I argue that decolonial love can provide a useful pedagogical framework for teaching sensitive and controversial topics since it ties together different approaches to teach such topics.
Keywords: Decolonial love; CAPS; History; Sensitive and controversial topics